1988
DOI: 10.2307/1511036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peer-Previewing on LD Students' Oral Reading Skills

Abstract: The effects of a peer-previewing system on the oral reading skills of three LD students were examined using a multiple-baseline design across subjects. Results indicated that peer-previewing led to a marked decrease in the oral reading errors of all subjects. Reasons for the effectiveness of the procedure as well as its advantages are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Using CBM, researchers have shown that several procedures can be used to improve oral reading rates in students with disabilities including modeling (e.g., Freeman & McLaughlin, 1984), listening previewing (e.g., Daly & Martens, 1994), peer previewing (e.g., Salend & Nowak, 1988) and classwide peer tutoring (e.g., Greenwood et al, 1987). One characteristic that each of these interventions have in common is that they provide students with additional opportunities to read.…”
mentioning
confidence: 99%
“…Using CBM, researchers have shown that several procedures can be used to improve oral reading rates in students with disabilities including modeling (e.g., Freeman & McLaughlin, 1984), listening previewing (e.g., Daly & Martens, 1994), peer previewing (e.g., Salend & Nowak, 1988) and classwide peer tutoring (e.g., Greenwood et al, 1987). One characteristic that each of these interventions have in common is that they provide students with additional opportunities to read.…”
mentioning
confidence: 99%
“…Existing data suggest that oral previewing promotes oral reading and comprehension (Reitsma, 1988;Rose, 1984;Rose & Beattie, 1986;Salend & Nowak, 1988). Similar to repeated readings, oral previewing incorporates repeated exposures to the same text.…”
Section: Oral Previewingmentioning
confidence: 99%
“…However, this study was of short duration and did not examine transfer effects to new reading materials. What is clear from the literature is that oral previewing does promote the oral reading and comprehension of normal and low performing readers (Rose, 1984;Rose & Beattie, 1986;Salend & Nowak, 1988). The benefits of oral previewing may be particularly important for extremely dysfluent students (i.e., students who read less than 45 words per minute) (Dowhower, 1987).…”
Section: Oral Previewingmentioning
confidence: 99%
“…In terms of prereading activities, Salend and Nowak ( 1988) investigated the effects of having an LD student who was a more proficient reader orally preview a passage with an LD student who was a less proficient reader. While the previewer read a passage aloud, the other student listened and followed along using a photocopy of the passage.…”
Section: Impact Of Peers On Pupil Pursuitsmentioning
confidence: 99%